Profiling of anti-oxidative enzymes and lipid peroxidation in leaves of salt tolerant and salt sensitive maize hybrids under NaC1 and Cd stress - Abbasi, Ghulam Hasan; Ijaz, Muhammad; Akhtar, Javaid; Anwar Ul-Haq, Muhammad; Jamil, Moazzam; Ali, Shafaqat; Ahmad, Rafiq; Nawaz Khan, Hammad (Universiti Kebangsaan Malaysia, 2016)
Effects of NaCl salinity and cadmium on the anti-oxidative activity of enzymes like superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), glutathione reductase (GR) and lipid peroxidation contents; malondialdehyde (MDA) were studied in two maize hybrids of different salt tolerance characteristics. An increase in the amount of lipid peroxidation indicated the oxidative stress induced by NaCl and Cd. The results also depicted that NaCl stress caused an increase in the activities of POD, SOD, CAT, APX and GR while cadmium stress increased the activities of POD, SOD and APX but showed no significant effect on CAT and GR in both the studied hybrids. The combined effect of salinity and cadmium on these parameters was higher than that of sole effect of either NaCl or Cd. It was also found that maize hybrid 26204 had better tolerance against both stresses with strong antioxidant system as compared to that of maize hybrid 8441. A comparison of the antioxidants and lipid peroxidation in two maize hybrids having varying level of NaCl and Cd stress tolerance corroborated the importance of reactive oxygen species (ROS) in defense against abiotic stresses.